Grief interventions for people bereaved by suicide: A systematic review. - Katja Linde; Julia Treml; Jana Steinig; Michaela Nagl; Anette Kersting (PLoS ONE, 2017)
Background Adaption to the loss of a loved one due to suicide can be complicated by feelings of guilt, shame, responsibility, rejection, and stigmatization. Therefore people bereaved by suicide have an increased risk for developing complicated grief which is related to negative physical and mental disorders and an increased risk for suicidal behavior. Grief interventions are needed for this vulnerable population. The aim of this systematic review was to provide an overview of the current state of evidence concerning the effectiveness of interventions that focus on grief for people bereaved by suicide. Methods We conducted a systematic literature search using PubMed, Web of Science, and PsycINFO for articles published up until November 2016. Relevant papers were identified and methodological quality was assessed by independent raters. A narrative synthesis was conducted. Results Seven intervention studies met the inclusion criteria. Two interventions were based on cognitive-behavioral approaches, four consisted of bereavement groups, and one utilized writing therapy. As five of the seven interventions were effective in reducing grief intensity on at least one outcome measure, there is some evidence that they are beneficial. Bereavement groups tend to be effective in lowering the intensity of uncomplicated grief, as are writing interventions in lowering suicide-specific aspects of grief. Cognitive-behavioral programs were helpful for a subpopulation of people who had high levels of suicidal ideation. Limitation On average, methodological quality was low so the evidence for benefits is not robust. The stability of treatment effects could not be determined as follow-up assessments are rare. Generalizability is limited due to homogeneous enrollments of mainly female, white, middle-aged individuals. Conclusions People bereaved by suicide are especially vulnerable to developing complicated grief. Therefore, grief therapies should be adapted to and evaluated in this population. Prevention of complicated grief may be successful in populations of high risk individuals.